Macrophage-secreted cytokines drive pancreatic acinar-to-ductal metaplasia through NF-κB and MMPs - Liou, Geou-Yarh (The Rockefeller University Press, 2013)
In response to inflammation, pancreatic acinar cells can undergo acinar-to-ductal metaplasia (ADM), a reprogramming event that induces transdifferentiation to a ductlike phenotype and, in the context of additional oncogenic stimulation, contributes to development of pancreatic cancer. The signaling mechanisms underlying pancreatitis-inducing ADM are largely undefined. Our results provide evidence that macrophages infiltrating the pancreas drive this transdifferentiation process. We identify the macrophage-secreted inflammatory cytokines RANTES and tumor necrosis factor α (TNF) as mediators of such signaling. Both RANTES and TNF induce ADM through activation of nuclear factor κB and its target genes involved in regulating survival, proliferation, and degradation of extracellular matrix. In particular, we identify matrix metalloproteinases (MMPs) as targets that drive ADM and provide in vivo data suggesting that MMP inhibitors may be efficiently applied to block pancreatitis-induced ADM in therapy.